A bi-continuous network structure of p-DTS(FBTTh2)2/EP-PDI via selective solvent vapor annealing. Issue 42 (17th October 2016) - Li, Mingguang; Liang, Qiuju; Zhao, Qiaoqiao; Zhou, Ke; Yu, Xinhong; Xie, Zhiyuan; Liu, Jiangang; Han, Yanchun
Abstract : Donor selective solvent vapor annealing leads to the moderate phase-separated morphology accompanied by a pure crystalline phase with a medium size, which could maximize the carrier transport process without compromising exciton separation efficiency. Abstract : A critical requirement of small molecule non-fullerene acceptor-based solar cells for efficient charge separation and collection is the formation of interconnected phase-separated domains of 10–20 nm. The phase-separation behavior of small molecule donor 7, 7′-(4, 4-bis(2-ethylhexyl)-4 H -silolo[3, 2- b :4, 5- b ′]dithiophene-2, 6-diyl)bis(6-fluoro-4-(5′-hexyl-[2, 2′-bithiophen]-5-yl)benzo[ c ][1, 2, 5]thiadiazole) ( p -DTS(FBTTh2 )2 ) and acceptor N, N ′-bis(1-ethylpropyl)-perylene-3, 4, 9, 10-tetracarboxylic diimide (EP-PDI) was regulated by donor selective solvent vapor annealing (D-SVA), poor donor solvent vapor annealing (P-SVA) and thermal annealing (TA). It was found that the power conversion efficiency (PCE) was significantly improved from less than 0.2% up to 3.0% after D-SVA. In contrast, a limited improvement of PCE was obtained for P-SVA (1.9%) and TA (1.8%). The difference in the improvement of PCE values was attributed to the formation of a phase-separated structure and the regulation of crystallite sizes under different post treatments. The fibrous crystals of p -DTS(FBTTh2 )2 were formed during D-SVA treatment while the EP-PDI component was in the form of small microcrystals, thus leading to the required interconnected phase-separated structure. As a consequence, the moderate phase-separated morphology accompanied by a pure crystalline phase with a medium size could maximize the carrier transport process without compromising exciton separation efficiency, and thus contributes to the final optimal PCE value of up to 3.0% under D-SVA. For P-SVA or TA treatment, we only observed a significant enhancement of the crystallinity of both p -DTS(FBTTh2 )2 and EP-PDI components, leading to remarkable film coarsening, or even undesired large phase separation, which is detrimental to the exciton diffusion as well as exciton separation processes.